Maternal Interaction With Infants Among Women at Elevated Risk for Postpartum Depression - Goodman, Sherryl H.; Muzik, Maria; Simeonova, Diana I.; Kidd, Sharon A.; Owen, Margaret Tresch; Cooper, Bruce; Kim, Christine Y.; Rosenblum, Katherine L.; Weiss, Sandra J. (Frontiers in Psychology, 2022)
Ample research links mothers’ postpartum depression to adverse interactions with their infants. However, most studies relied on general population samples, whereas a substantial number of women are at elevated depression risk. The purpose of this study was to describe mothers’ interactions with their 6- and 12-month old infants among women at elevated risk, although with a range of symptom severity. We also identified higher-order factors that best characterized the interactions and tested longitudinal consistency of these factors from 6 to 12 months of infant age. We leveraged data from 8 projects across the U.S. (n = 647), using standardized depression measures and an adaptation of the NICHD Mother-Infant Interaction Scales. Overall, these depression-vulnerable mothers showed high levels of sensitivity and positive regard and low levels of intrusiveness, detachment and negative regard with their infants. Factor analyses of maternal behaviors identified two overarching factors - ‘positive engagement’ and ‘negative-intrusiveness’ that were comparable at 6 and 12 months of infant age. Mothers’ ability to regulate depressed mood was a key behavior that defined ‘positive engagement’ in factor loadings. An exceptionally strong loading of intrusiveness on the second factor suggested its central importance for women at elevated depression risk. Mothers with severe depressive symptoms had significantly more ‘negative-intrusiveness’ and less ‘positive engagement’ with their 6-month old infants than women with moderate or fewer depressive symptoms, suggesting a potential tipping point at which symptoms may interfere with the quality of care. Results provide the foundation for further research into predictors and moderators of women’s interactions with their infant among women at elevated risk for postpartum depression. They also indicate a need for evidence-based interventions that can support more severely depressed women in providing optimal care.